Scientific Neutrality in the Age of Artificial Intelligence: A Critical Analysis of the Value-Free Ideal - Harto, Budi; Ahida, Ridha (Sekolah Tinggi Ilmu Tarbiyah (STIT) Ahlussunnah Bukittinggi, 2025)
The debate on the neutrality of scientific knowledge whether science is value-free or value-laden has been a central discussion in the philosophy of science from the era of logical positivism to the present. The positivist tradition of Carnap and Reichenbach, along with Popper’s falsificationism, argues that the process of scientific justification must be separated from non-epistemic values in order to secure objectivity. However, the use of artificial intelligence (AI) in contemporary scientific research presents empirical evidence that challenges this ideal of value-free science. This study critically examines how the use of AI in science supports the value-laden position advocated by Thomas Kuhn, Helen Longino, and feminist epistemology. Employing a qualitative method with a content analysis approach, the study is analyzed through a philosophical analytical framework. The findings identify three major positions: neopositivism, which defends the value-free ideal; the Kuhnian position, which acknowledges the role of epistemic values; and the radical value-laden position. The discussion demonstrates that artificial intelligence substantiates the value-laden view through four dimensions: algorithmic bias as a manifestation of social values, value-laden design choices in artificial intelligence systems, the incommensurability of artificial intelligence paradigms, and situated objectivity, which requires explicit recognition of embedded values. The study concludes that artificial intelligence not only confirms but reinforces the argument that the value-free ideal is a philosophical illusion, and that responsible science requires critical reflexivity toward the values embedded within scientific practice.